Conservative Management of Large Rectosigmoid Perforation under Peritoneal Reflection: Case Report and Review of the Literature - G. G. Akgul; E. Yenidogan; Z. Ozsoy; I. Okan; H. A. Kayaoglu; S. Tali; M. Sahin (Case Reports in Surgery)
Colonoscopy is accepted as the best method in diagnosis, treatment, and follow-up of colorectal diseases. As the amount of the usage of diagnostic and therapeutic colonoscopy rises, iatrogenic complications are more likely to be seen. The most important complications are perforations and bleeding. Whereas perforation is a complication that is seen rarely, because of the high ratio of morbidity and mortality, it should be analyzed more carefully. There is not a common view on the optimal treatment of colonoscopic perforation. Most cases require urgent surgery, and in some cases the iatrogenic perforation of colon can be managed by conservative methods. In this report, we present a rectosigmoid perforation under peritoneal reflection and conservative management of this case.